Karakterisasi kandungan vitamin B12, folat dan isoflavon tempe kedelai dengan isolat murni Rhizopus oryzae, Rhizopus oligosporus, dan Rhizopus stolonifer sebagai bahan pangan fungsional - Vira Putri Yarlina; Dea Indriani Astuti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Tempeh is a fermented food ingredient from soybeans that uses various Rhizopus molds, such as Rhizopus oligosporus, Rhizopus oryzae, Rhizophus stolonifer. In this study, the preparation of tempe using mixed culture was carried out in the ratio of Rhizopus oryzae, Rhizopus oligosporus, Rhizopus stolonifer inoculums, namely 1: 1: 1; 1: 2: 1; 2: 1: 2; 1: 1: 2; 2: 1: 1; market yeast "Raprima", produces the characteristics of tempe according to SNI 01-3144-2009, formation of Vitamin B12, Folate and Isoflavones as well as pH, and Total Bacteria. The content of vitamin B12 was obtained in yeast "raprima" of 0.013 g / 50g of tempeh while tempeh made with pure inoculums of Rhizopus sp did not contain vitamin B12 or folic acid, pH value of 4.2 and total bacteria 14.3x108 cfu / ml and organoleptic reception. Tempe 1: 2: 1 has the characteristics of color, aroma, taste, texture and viscosity acceptable to the panelists.